PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI BAGIAN TENAGA PENDIDIK PADA YAYASAN AL-AMIEN SMK TARUNA BHAKTI CIKARANG - Azzahra, Andrea Veren; Raharja, Irwan (Ekonis: Jurnal Ekonomi dan Bisnis, 2024)
Abstract: This study aims to test and analyze the influence of leadership style and work discipline on employee performance. This study was conducted at the Al-Amien Foundation, SMK Taruna Bhakti Cikarang. This study uses a quantitative approach. The sample used was 42 respondents, the data was distributed using a questionnaire via Google form. Data were collected with a questionnaire that had been tested for validity and reliability. The data analysis technique used was multiple regression. Based on the SPSS22 output, the results of the study showed that the leadership style variable with a t count of 3.913 r table 2.023 and a significance level of t less than 0.05 (sig. T = 0.000 0.05), it was concluded that leadership style partially had a significant positive effect on employee performance. While the work discipline variable with a t count of 4.933 r table 2.023 and a significance level of t less than 0.05 (sig. T = 0.000 0.05), it was concluded that leadership style partially had a significant positive effect on employee performance. The results of the study showed that the F-count (F-statistic) of 12.997 was greater than the F table of 3.24 with a significance value of 0.000. It was concluded that leadership style and work discipline simultaneously (together) had a positive and significant effect on employee performance. Keywords: Leadership Style, Work Discipline, Employee Performance